Going organic: mobilizing networks for environmentally responsible food production - Lockie, S.; Halpin, D.; Halpin, D.; Lawrence, G.; Lawrence, G.; Lockie, S.; Lyons, K.; Lyons, K. (Wallingford :CABI, 2006)
This book sets out to assess the current situation of the organic agriculture/food sector, debunking a number of apparently common sense beliefs in the process, viz. that organic consumers are wealthy environmental and health extremists; that growth in the industry will inevitably undermine its environmental values; that the mainstream media are antagonistic to organics; and that the industry is driven by consumer demand. This book aims to make a practical contribution to the development of more sustainable food systems by exploring and revealing what it takes to get people involved in organics at each stage of the food chain.
Keywords: EE110 - Agricultural Economics; EE116 - Food Economics, (New March 2000); EE700 - Marketing and Distribution; EE720 - Consumer Economics